Pengaruh Pemberian Tablet Fe Terhadap Hemoglobin Pada Taruni Politeknik Ilmu Pelayaran Semarang - Anggi Vina Hariyati; Cahyaningrum; Adil Zulkarnain (Universitas Ngudi Waluyo, 2020)
Anemia is one of the public health problems that need more attention of the female because they experience menstruation and they are in the growth phase. From the data of Semarang City Health Office in 2011, it is shown the incidence of anemia in adolescents aged 10-19 years old are 68.24%. The prevention effort of the case is by measuring hemoglobin and prescribing blood supplement. The objective of the study is to find out the effect of Fe tablets on Hemoglobin in Semarang Merchant Marine Polytechnique students. The objective of the study is to find out the effect of Fe tablets on Hemoglobin in Semarang Merchant Marine Polytechnique students. This research used pre-experimental design with the two group pretest posttest. The population in this Study were all Merchant Marine Polytechnique Semarang at the 4th semester of female students amounting to 50 with the total respondents 34 respondents taken with purposive sampling technique. The data were collected by performing Hemoglobin examination. The results of the study show that the average Hemoglobin before being prescribed Fe on the intervention and control group was 11.29 g/dl. After being prescribed Fe to the intervention group, it is found the average increased to 13.69 g/dl, while in the control group it is found averaged 11.72 g/dl. Bivariate Analysis uses an independent t test, the value of t is 6.136 with a p-value of 0.000. It shows that the p-value is 0,000 <((0.05), this indicates that there is a significant difference in the decrease in Hemoglobin levels in the population after being prescribed blood supplement between the intervention and control groups in The Semarang Merchant Marine Politechnique Students. It is suggested that the female adolescents to consume more iron-containing foods or consume Fe supplements such as Fe, during menstruation. ABSTRAK Anemia merupakan salah satu masalah kesehatan masyarakat yang perlu khusus nya pada remaja putri yang perlu mendapatkan perhatian khusus karena remaja putri mengalami mestruasi tiap bulan dan dalam masa pertumbuhan . Hasil Data Dinas Kesehatan Kota Semarang tahun 2011. Kejadian anemia pada remaja usia 10-19 sebanyak 68,24%. Untuk menangani masalah tersebut pencegahan yang dilakukan yaitu dengan cara mengukur hemoglobin dan pemberian suplemen tablet tambah darah . Penelitian ini bertujuan untuk melihat Pengaruh Pemberian Tablet Fe Terhadap Hemoglobin Pada Taruni Politeknik Ilmu Pelayaran Semarang. Penelitian ini bertujuan untuk melihat Pengaruh Pemberian Tablet Fe Terhadap Hemoglobin Pada Taruni Politeknik Ilmu Pelayaran Semarang. Jenis penelitian ini menggunakan pre-eksperimen design dengan rancangan Two group pretest posttest. Populasi dalam penelitian iniadalah seluruh taruni politeknik ilmu pelayaran semarang semester 4 berjumlah 50 taruni dengan jumlah sempel 34 responden dengan tehnik pengambilan sempel purposive sampling. Pengambilan data dengan melakukan pemeriksaan Hemoglobin. Penelitian menunjukan bahwa rata-rata Hemoglobin sebelum diberikan pada taruni kelompok intervensi dan kontrol sama yaitu 11,29 g/dl. Dan setelah diberikan pada kelompok intervensi rata-rata meningkat menjadi 13,69 g/dl, sedangkan kelompok kontrol rata-rata sebesar 11,72 g/dl. Analisis bivariate Menggunakan uji t independen, didapatkan nilai t hitung 6,136 dengan p-value sebesar 0,000. Terlihat bahwa p-value 0,000 <a (0,05), ini menunjukkan bahwa ada perbedaan secara signifikan penurunan (selisih) kadar Hemoglobin b pada taruni sesudah diberikan tablet penambah darah antara kelompok intervensi dan kontrol pada taruni Politeknik Ilmu Pelayaran Semarang. Hendaknya bagi remaja putri lebih banyak mengomsumsi makanan yang mengandung zat besi atau mengomsumsi suplemen yang mengandung besi seperti Fe terutama saat mestruasi